2006
DOI: 10.1021/bp050296i
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Equally Sized Particle Plaques Using Solid-Liquid Suspensions

Abstract: A device is presented for the generation of equally sized plaques of sensitive particles in a 96-well format. The resulting particle plaques can be used for the measurement of adsorption isotherms and uptake kinetics in protein chromatography or for immobilization reactions. The particle plaques are formed from suspensions with a vacuum device that is designed as a reusable sandwich module. The particles are retained by a mesh while the solvent is removed by the vacuum. As most particles used for protein chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 7 publications
5
16
0
Order By: Relevance
“…Finally, pipetting of slurries expresses a high potential for experimental errors. In contrast, the use of resin plaques of defined volume prepared prior to an experimental study has shown to express a superior performance and eliminates the above mentioned drawbacks [28]. Plaques are generated using a grid in 96-well plate format with holes of a defined volume.…”
Section: Plate Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, pipetting of slurries expresses a high potential for experimental errors. In contrast, the use of resin plaques of defined volume prepared prior to an experimental study has shown to express a superior performance and eliminates the above mentioned drawbacks [28]. Plaques are generated using a grid in 96-well plate format with holes of a defined volume.…”
Section: Plate Handlingmentioning
confidence: 99%
“…Plaques are generated using a grid in 96-well plate format with holes of a defined volume. The holes are then filled with the respective resins by using vacuum [28] or centrifugal force [29].…”
Section: Plate Handlingmentioning
confidence: 99%
“…A vacuum plaque device was used to generate equally sized adsorbent plaques with a volume of 8.8 L each (20). The plaques were equilibrated within the plaque device with 100 mM Tris-HCl buffer, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…As the 36 plaques at the border of the ResiQuot device show slightly higher variances in shape and weight (see [18]), they were completely left out in experimentation, thus only the 60 inner plaques in the deep-well plate (DWP) were used for the binding studies. S1a in the Supporting Information illustrates the size and appearance of typical adsorbent plaques.…”
Section: Apparatus and Softwarementioning
confidence: 99%